Management of the Saddang River Sand Mining Area, Pinrang Regency, South Sulawesi - Arsyad; Ruslan Bauna; Hamzah; Muh. Aris Arifin; Jamaluddin; Eris Nurdirman; Reno (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the research is to obtain an overview of the condition of the Saddang River in order to manage the sand mining area, taking into account environmental, economic and socio-social aspects. Various studies show that river sand mining can provide direct and indirect economic benefits to local communities, as well as environmental damage to rivers. However, research on Saddang River sand mining is still very minimal. The data collection methods used consist of literature studies to collect various reading materials that support and support research, field surveys to obtain data directly from the field, presentation of question sheets (questionnaires) and interviews on issues that are in accordance with the research theme. Focus Group Discussion (FGD) to examine stakeholders and local communities. Physical condition of the river body and replenishment rate using UPTD data for the Saddang Watershed. Management with an integrated approach includes economic, environmental and social-social aspects, by combining two different paradigm approaches, namely positivistic and constructivist, which is believed to be able to produce a sustainable management strategy for sand mining activities in the Saddang River, Pinrang Regency.